Observing flow using fast neutron radiography and positron emission particle tracking - Daniels, Graham Clinton (Department of Physics, 2021)
Dynamic flow of material has been studied using fast neutron radiography (FNR) and positron emission particle tracking (PEPT). A new fast neutron imaging system was commissioned at The South African Nuclear Energy Corporation, Pretoria, as part of this study, although FNR measurements were ultimately performed at PhysikalischTechnische Bundesanstalt (PTB), Braunschweig. The PEPT studies were undertaken at the PEPT Cape Town facility located at iThemba LABS, Cape Town. The steady state motion of media, within a laboratory-scale tumbling mill, was studied for a range of speed and media mixes, using both FNR and PEPT. Several operational parameters were derived from the data, which could be related to potential improvements to the milling efficiency. The blending of FNR and PEPT data for the study of steady state flow, was explored for the first time. In addition, the flow of water through porous media was studied using FNR, which enabled the determination of the hydraulic conductivity, and hence intrinsic permeability, of the media within the column. The potential of using FNR, without or without PEPT, for the study of material in motion is discussed.